How can we increase girls' uptake of maths and physics A-level? - Rachel Cassidy; Sarah Cattan; Claire Crawford; Siobham Dytham (Institute for Fiscal Studies (IFS), 2018)
There is a large gender gap in the likelihood of taking maths and physics at A-level, even among high-achieving pupils. Among pupils who achieved grade A or A* (equivalent to grades 7-9) in GCSE maths in 2010, 36.5% of girls compared to 51.1% of boys took maths A-level. Among those who achieved grade A or A* in GCSE physics, just 13.2% of girls compared to 39.3% of boys took physics A-level. By contrast, there is almost no gender gap in the likelihood of taking chemistry A-level amongst those who score highly in the subject at GCSE, and girls are actually more likely to take biology A-level than boys. In partnership with the STEM Skills Fund, we conducted a study to understand the barriers that stop girls from taking maths and physics at A-level. This took the form of a small-scale randomised control trial in which girls in Year 11 who were predicted to achieve at least grade 7 (equivalent to at least grade A) in maths, physics or combined science GCSE were offered financial support in return for applying to study physics or maths A-level. As part of this trial, we surveyed 266 girls, as well as a senior staff member across 40 schools, about girls' A-level subject choices and what drives them. We also conducted four focus groups with 6-8 girls in schools in Bolton, Hull, Birmingham and Portsmouth to discuss these reasons in more detail.
Keywords: 330